Al-Tafkīr al-Fiqhīyah ‘inda Nahdlatul Ulama - Hodri Ariev (Studia Islamika, 1999)
Since its establish in 1926, Nahdatul Ulama (NU) has been known as a socio-religious organization that bases its thought and practice on the four outstanding Islamic law school: Maliki, Shafi'i and Hanafi. However, during the third NU's Congress in Surabaya, East JAva, NU declared itself to affiliated to Shafi its school only. The congress was special because this declaration was incorporated formally into its constitution; the Congress also resulted in the creation of a special forum to discuss religious legal problems (bahtsul masail Ar. bahth al-masa'il) faced by ummah. To date not less than 420 decisions have been produced by this forum that adress various problems such as family, politics, economy, education, ritual and so forth.DOI: 10.15408/sdi.v6i1.749